A novel hemA mutation is responsible for a small-colony-variant phenotype in Escherichia coli. Issue 3 (7th March 2021) - Hubbard, Alasdair T. M.; Bulgasim, Issra; Roberts, Adam P.
Abstract : We identified a small colony variant (SCV) of an amoxicillin/clavulanic acid-resistant derivative of a clinical isolate of Escherichia coli from Malawi, which was selected for in vitro in a subinhibitory concentration of gentamicin. The SCV was auxotrophic for hemin and had impaired biofilm formation compared to the ancestral isolates. A single novel nucleotide polymorphism (SNP) in hemA, which encodes a glutamyl-tRNA reductase that catalyses the initial step of porphyrin biosynthesis leading to the production of haem, was responsible for the SCV phenotype. We showed the SNP in hemA resulted in a significant fitness cost to the isolate, which persisted even in the presence of hemin. However, the phenotype quickly reverted during sequential sub-culturing in liquid growth media. As hemA is not found in mammalian cells, and disruption of the gene results in a significant fitness cost, it represents a potential target for novel drug development specifically for the treatment of catheter-associated urinary tract infections caused by E. coli .